Pemeriksaan Kesehatan Dasar Bagi Masyarakat Dalam Rangka Meningkatkan Kesadaran Hidup Sehat - Centia Komalasari; Desy Merilla Erizon; Kurniati Maya Sari; Netty Herawati; Ginda Sofia; Ami Wulan Sari (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
Health is a fundamental right of every individual and a key determinant of quality of life. However, in reality, awareness of early detection of health conditions remains very low. Many people only seek medical check-ups when they experience symptoms or are in a serious condition. In fact, various non-communicable diseases such as hypertension, diabetes mellitus, and obesity can be prevented and controlled if detected early through regular basic health check-ups. The number of non-communicable diseases (NCDs) in Indonesia in 2023 shows that NCDs are the leading cause of death in Indonesia, with 73% of deaths caused by NCDs. This activity is expected to increase public awareness and proactiveness in maintaining their health from an early age. This activity also supports the national health development goal of improving public health to the highest level. This community service activity consists of simple medical check-ups such as height and weight checks, waist circumference checks, blood pressure checks, fasting blood glucose, cholesterol, and uric acid checks. The aim is to determine the community's health status, thereby increasing public awareness and allowing for further treatment related to these health conditions. This activity was carried out in the community of Jorong Pamujan Kenagarian Kinari, Solok Regency. Conclusion: Free health screenings were conducted, including height and waist circumference checks, blood pressure checks, and blood tests (fasting blood glucose, cholesterol, and uric acid). Recommendation: Maintain good health to prevent disease and conduct regular checkups for residents with high blood pressure and diabetes mellitus.